Truth v. justice the morality of truth commissions - edited by Robert I. Rotberg (Princeton Princeton University Press, 2000)
The truth commission is an increasingly common fixture of newly democratic states with repressive or strife-ridden pasts. From South Africa to Haiti, truth commissions are at work with varying degrees of support and success. To many, they are the best--or only--way to achieve a full accounting of crimes committed against fellow citizens and to prevent future conflict. Others question whether a restorative justice that sets the guilty free, that cleanses society by words alone, can deter future abuses and allow victims and their families to heal. Here, leading philosophers, lawyers, social scientists, and activists representing several perspectives look at the process of truth commissioning in general and in post-apartheid South Africa. They ask whether the truth commission, as a method of seeking justice after conflict, is fair, moral, and effective in bringing about reconciliation.
Includes bibliographical references and index.
Keywords: South Africa. Truth and Reconciliation Commission